Impact of local anesthesia block on pain medication use and length of hospital stay in elderly indigenous patients in Alaska hospitalized for fragility fracture. Issue 4 (19th December 2022) - Young, Aimee; Robinson, Renee; Nguyen, Elaine; Stewart, Eric; Lin, Ai-Ling; Locke, Michelle; Hurrell, Rowan
Abstract : Abstract: Introduction: Fragility fractures (low-energy, minimal-trauma fractures) are common in the aging population and can lead to decreased function, increased mortality, and long-lasting pain. Although opioids are helpful in reducing acute postoperative pain, they present risks that may lead to increased morbidity and mortality. Materials and Methods: This was a retrospective review of medical records of all Alaska Native and American Indian people older than 50 years, who received surgery for hip fracture repair between January 2018 and June 2019 (n = 128). Results: We found that receipt of a peripheral nerve block (PNB) is a predictor for decreased length of hospital stay. However, receipt of PNB did not predict a reduction in postoperative morphine milligram equivalents opioid doses. Discussion: Further study is required to determine whether one PNB method is superior to others based on individual-level characteristics.